2016
DOI: 10.1093/mnras/stw2830
|View full text |Cite
|
Sign up to set email alerts
|

Identifying fourINTEGRALsources in the Galactic plane via VLT/optical andXMM–Newton/X-ray spectroscopy

Abstract: We report on FORS2 spectroscopy aiming at the identification of four Galactic Plane sources discovered by INTEGRAL, IGR J18088−2741, IGR J18381−0924, IGR J17164−3803, and IGR J19173+0747, complemented by XMM-Newton spectroscopy for IGR J18381−0924. The presence of broad H i and He i emission lines and a flat Balmer decrement Hα/Hβ show that IGR J18088−2741 is a cataclysmic variable located beyond 8 kpc. For IGR J18381−0924, the detection of red-shifted Hα and O i emission signatures and the absence of narrow f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Regular observations of the GP with INTEGRAL are consistently improving the sensitivity of the hard X-ray survey and allowing us to extend our knowledge of the Galactic Xray source population, both for weak and nearby sources (mostly CVs, see e.g. Lutovinov et al 2010;Clavel et al 2016;Tomsick et al 2016a), and more distant objects located at far end of the Galaxy Rahoui et al 2017). The presented catalogue opens the path to a large program of follow-up observations, dedicated both to unveil new classes of objects and to increase the overall completeness of the source sample, needed for many Galactic population studies.…”
Section: Concluding Remarkmentioning
confidence: 98%
See 1 more Smart Citation
“…Regular observations of the GP with INTEGRAL are consistently improving the sensitivity of the hard X-ray survey and allowing us to extend our knowledge of the Galactic Xray source population, both for weak and nearby sources (mostly CVs, see e.g. Lutovinov et al 2010;Clavel et al 2016;Tomsick et al 2016a), and more distant objects located at far end of the Galaxy Rahoui et al 2017). The presented catalogue opens the path to a large program of follow-up observations, dedicated both to unveil new classes of objects and to increase the overall completeness of the source sample, needed for many Galactic population studies.…”
Section: Concluding Remarkmentioning
confidence: 98%
“…In the previous paper (Krivonos et al 2012), we pre- Lutovinov et al 2013b, for details). A number of multi-wavelength follow-up observations were initiated to unveil the nature of these unclassified objects (Karasev et al 2012;Masetti et al 2013;Revnivtsev et al 2013;Zolotukhin & Revnivtsev 2015;Lutovinov et al 2013aLutovinov et al , 2015Tomsick et al 2015Tomsick et al , 2016aClavel et al 2016;Burenin et al 2016;Rahoui et al 2017) which led to the classification of 11 sources (shown by solid red circles in Fig. 1), rising the total survey identification completeness from ∼92% to ∼94%.…”
Section: Introductionmentioning
confidence: 99%
“…After the aforementioned compilation by [114], [115] reported the first detection of the X-ray emission from eight more symbiotic systems using Swif t/XRT, thus bringing the total number of known symbiotic systems as X-ray sources to 33 (see also [38]). 561213) [120], IGR J17164-3803 [121] and IGR J17463-2854 [122].…”
Section: Symbiotic Starsmentioning
confidence: 99%